2019
DOI: 10.1021/acs.chemrestox.9b00171
|View full text |Cite
|
Sign up to set email alerts
|

Common E-Cigarette Flavoring Chemicals Impair Neutrophil Phagocytosis and Oxidative Burst

Abstract: E-cigarette flavorings have not been thoroughly evaluated for inhalational toxicity. We have shown that the flavoring chemical cinnamaldehyde impairs human neutrophils, macrophages, and natural killer cells. Here we investigated the effects of other common e-liquid flavoring chemicals on phagocytosis and oxidative burst in neutrophils. We demonstrate that cinnamaldehyde and ethyl vanillin dose-dependently decrease oxidative burst and that benzaldehyde and benzaldehyde propylene glycol acetal dose-dependently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…The flavoring chemicals diacetyl, benzaldehyde and acetyl propionyl, widely recognized as being associated with respiratory disease when inhaled, have all been identified in eliquids (Allen, Flanigan, LeBlanc, et al, 2016;Farsalinos, Kistler, Gillman, & Voudris, 2015). Indeed, individual flavors have been shown to cause significant cellular toxicity (Behar, Wang, & Talbot, 2018;Clapp, Lavrich, van Heusden, et al, 2019;Hickman, Herrera, & Jaspers, 2019). Moreover, a recent study demonstrated that e-cigarette liquids can be chemically unstable, with reactions occurring between flavor aldehydes and the e-liquid solvent propylene glycol resulting in flavor aldehyde propylene glycol acetals, stable in aqueous solutions for >36 hr, with subsequent adverse health consequences (Erythropel, Jabba, DeWinter, et al, 2018).…”
Section: Are Ends a "Safer Alternative" To Tobacco Smoking During Pmentioning
confidence: 99%
“…The flavoring chemicals diacetyl, benzaldehyde and acetyl propionyl, widely recognized as being associated with respiratory disease when inhaled, have all been identified in eliquids (Allen, Flanigan, LeBlanc, et al, 2016;Farsalinos, Kistler, Gillman, & Voudris, 2015). Indeed, individual flavors have been shown to cause significant cellular toxicity (Behar, Wang, & Talbot, 2018;Clapp, Lavrich, van Heusden, et al, 2019;Hickman, Herrera, & Jaspers, 2019). Moreover, a recent study demonstrated that e-cigarette liquids can be chemically unstable, with reactions occurring between flavor aldehydes and the e-liquid solvent propylene glycol resulting in flavor aldehyde propylene glycol acetals, stable in aqueous solutions for >36 hr, with subsequent adverse health consequences (Erythropel, Jabba, DeWinter, et al, 2018).…”
Section: Are Ends a "Safer Alternative" To Tobacco Smoking During Pmentioning
confidence: 99%
“…Similar effects were found for ethyl vanillin (vanilla flavors) and benzaldehyde (almond and cherry flavors). 73,74 The highest flavoring chemical exposures for the human cells used in the Jaspers lab were two orders of magnitude below the ranges reported for e-liquids and aerosols. 73 Several flavoring chemicals transfer from e-liquids into aerosols at high efficiency, with an average of 86% reported for some devices.…”
Section: Flavoring Chemicals and Interactions With Solventsmentioning
confidence: 89%
“…73,74 The highest flavoring chemical exposures for the human cells used in the Jaspers lab were two orders of magnitude below the ranges reported for e-liquids and aerosols. 73 Several flavoring chemicals transfer from e-liquids into aerosols at high efficiency, with an average of 86% reported for some devices. 75 However, the levels of these chemicals in biological specimens of e-cigarette users are currently unknown.…”
Section: Flavoring Chemicals and Interactions With Solventsmentioning
confidence: 89%
“…Indeed, there is already evidence connecting disruption of immunity mechanisms with the use of E-liquids where the effect of nicotine is laso suggested to not be the most important [40] [41]. The CC46 model could be useful for further studies into conserved pathways that are affected by using E-liquids.…”
Section: Discussionmentioning
confidence: 99%